Multiproxy studies of lake sediments during mid-Holocene in Zhengzhou region of the Henan Province, central China, and the implications for reconstructing the paleoenvironments. (30th June 2019) - Wang, Longsheng; Hu, Shouyun; Yu, Ge; Wang, Xiaohui; Wang, Qing; Zhang, Zhenhua; Ma, Mingming; Cui, Buli; Liu, Xianbin
Abstract: The Holocene environmental evolution of the Zhengzhou region that is a major birthplace of Chinese civilization is of great interest to a wide community. In this study, we conducted a systematic investigation on grain size, total organic carbon (TOC), geochemistry, pollen and magnetic minerals of core PT sediments from the Zhengzhou region of the Henan Province in central China. Five units of sedimentary facies are identified as alluvial deposit, lacustrine deposit, swamp deposit, lacustrine deposit and alluvial deposit from bottom to top. Magnetic measurements indicate that magnetite and hematite dominate the magnetic mineral assemblages. The lacustrine and swamp deposits (1380-640 cm) were AMS 14 C dated to 5580-2670 yr BP and the chronology is further corroborated by the pedostratigraphic correlation to the adjacent cores in Zhengzhou region. Palynologically speaking, the period from 5580 to 5210 yr BP was characterized by lowest pollen percentages of Artemisia, Chenopodiaceae, Gramineae and Cyperaceae, higher values in clay contents, Sr contents and Fe/Mn ratios and also contents of magnetic mineral. The period from 5210 to 4760 yr BP was typified by rapid increases in Typha, Myriophyllum, Artemisia and Cyperaceae pollen percentages, gradual increases in ARM/SIRM and ARM/χ values, drastic drops in χ, ARM and SIRM values, with rather high values in clay contents, Sr contents and Fe/Mn ratios. The period between 4670 and 2670 yr BP was featured by gradual decreases in Gramineae, Artemisia, Typha and Myriophyllum pollen percentages, and increasing trends of χ, ARM and SIRM values, and decreasing trends of ARM/χ and ARM/SIRM values. Tracing the environmental changes since the mid-Holocene in the Zhengzhou region can provide an environmental reference for studying the human societal development in this birthplace of Chinese civilization.